VEGF Concentration in a Preovulatory Leading Follicle Relates to Ovarian Reserve and Oocyte Maturation during Ovarian Stimulation with GnRH Antagonist Protocol in In Vitro Fertilization Cycle - Wen-Bin Wu (MDPI AG, 2021)
Serum vascular endothelial growth factor (VEGF) is involved in follicular vascularization, oxygenation, and consequently in oocyte maturation and embryo development. Unanswered questions remain regarding the relationship of intrafollicular VEGF level in preovulatory leading follicles to oocyte maturation and ovarian reserve during ovarian stimulation. We conducted this study to investigate the relationship of intrafollicular VEGF level in the fluid of single preovulatory leading follicles to ovarian reserve and oocyte maturation in patients receiving GnRH antagonist in vitro fertilization (IVF) protocol treatment. One hundred and eighty-five patients receiving IVF treatment were recruited and assigned to low-, normal-, and high-ovarian-reserve groups according to their serum anti-Müllerian hormone (AMH) level. Follicular fluid (FF) in preovulatory leading follicles, serum profiles, and clinical variables were collected for analysis. The result disclosed a significant among-group difference in FF VEGF concentration. Moreover, the serum AMH level was also negatively correlated with FF VEGF level. The oocyte maturation rate tended to be increased at higher AMH levels. FF VEGF concentration was significantly positively correlated with basal FSH level. In conclusion, FF VEGF concentration has a negative association with ovarian reserve level and oocyte maturation rate in patients undergoing GnRH antagonist IVF protocols.